Understanding networked multimedia : applications and technology - Fluckiger, Franc?ois. (London ; New York : Prentice Hall, 1995)
Covers all networking, multimedia applications and technology in one volume. Has a tutorial approach to the subject, complete with formal definitions, glossary (500 terms), 230 illustrations, a list of frequently asked questions, real world examples and analogies, and end-of-chapter summaries. Sophisticated technologies are explained in a rigorous but easy-to- understand way. Network managers and administrators handling private and public LANs or WANs, system designers, computer industry product developers, and multimedia IS managers.
Includes bibliographical references (p. 605-611) and index.
1
Keywords: CIT; Multimedia systems; Computer networks